2017
DOI: 10.1136/bmjopen-2016-012694
|View full text |Cite
|
Sign up to set email alerts
|

Association of passive and active smoking with self-rated health and life satisfaction in Iranian children and adolescents: the CASPIAN IV study

Abstract: ObjectiveTo assess the joint association of passive and active smoking with self-rated health and life satisfaction among Iranian children and adolescents.MethodsUsing a multistage random cluster sampling method, a representative sample of 14 880 school students were selected from urban and rural areas of 30 provinces of Iran. Data were gathered using a questionnaire, a weight scale and metre. Participants were classified into four groups based on their smoking patterns: ‘non-smoker’, ‘only active smoker’, ‘on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 43 publications
(37 reference statements)
1
17
0
1
Order By: Relevance
“…TSE negatively impacts adolescents' overall health and physical health. 1,10 We found that TSE translated into a lower likelihood of having very good or excellent overall health and physical health status, as hypothesized. We found that regardless of TSE measure, adolescents with TSE reported that it was harder to exercise compared with peers and wheezing during or after exercise.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…TSE negatively impacts adolescents' overall health and physical health. 1,10 We found that TSE translated into a lower likelihood of having very good or excellent overall health and physical health status, as hypothesized. We found that regardless of TSE measure, adolescents with TSE reported that it was harder to exercise compared with peers and wheezing during or after exercise.…”
Section: Discussionsupporting
confidence: 64%
“…9 Active and passive smoking have been associated with lower overall health. 10 It is important to assess the relationship between types of TSE and potential TSE-attributable symptoms and other health indicators to inform intervention content that is aimed at reducing TSE among adolescents without asthma diagnoses.…”
mentioning
confidence: 99%
“…We found that adolescent ever and current smokers were at increased odds of self-selfreportingreporting good/fair/poor health status, aligning with prior research. 6 Results also indicated ever and current smokers were more likely to have had illness-related school absenteeism within the past month. This study expands on well-known school-related factors (eg, academic achievement) [7][8][9][10][11] by focusing solely on health-related absenteeism.…”
Section: Discussionmentioning
confidence: 94%
“…2 Active smoking has been related to lower self-reported health during adolescence. 6 It is well established that adolescents with low academic performance and grade level retention are at increased risk of smoking. [7][8][9][10][11] However, less is known on the association between smoking and illness-related school absenteeism.…”
Section: Introductionmentioning
confidence: 99%
“…Which of the following people you consider smokers? : According to WHo, a smoker is a person who smokes tobacco, either daily or occasionally(r. Heshmat et. al.…”
Section: Resultsmentioning
confidence: 99%